STRUCTURAL CONTROL ON BULK MELT PROPERTIES: SINGLE AND DOUBLE QUANTUM 29SI NMR SPECTROSCOPY ON ALKALI-SILICATE GLASSES - Malfait W.J.; Halter W.E.; Morizet Y.; Meier B.H.; Verel R. (My University, 2007)
The structure of 21 binary potassium, rubidium and cesium silicate glasses (in the range 15-50 mol% alkali oxide) was analyzed by 29Si single quantum and double quantum MAS NMR spectroscopy. Their glass transition temperatures (Tg) were measured by calorimetry. The chemical shifts and the relative abundance of Qn species correlate with the cationic field strength (Z/r) of the network modifier. A correlation is observed between Tg and the inverse of the entropy of mixing of the different Qn species, which is explained in the framework of the Adam-Gibbs relaxation theory. At high alkali content, up to 44% of the SiO4 tetrahedra are part of three-membered rings. At a given alkali content, the abundance of these rings increases with increasing cation size. The abundance of three-membered rings in K-silicate melts correlates with a temperature and a non-linear composition dependence of the heat capacity. It is also a possible cause for the anomalous volumetric behavior of potassium silicate glasses. © 2007 Elsevier Ltd. All rights reserved.